1997
DOI: 10.1016/s0550-3213(97)00220-4
|View full text |Cite
|
Sign up to set email alerts
|

R-R scalars, U-duality and solvable Lie algebras

Abstract: We consider the group theoretical properties of R-R scalars of string theories in the low-energy supergravity limit and relate them to the solvable Lie subalgebra G s ⊂ U of the U-duality algebra that generates the scalar manifold of the theory: exp[G s ] = U/H. Peccei-Quinn symmetries are naturally related with the maximal abelian ideal A ⊂ G s of the solvable Lie algebra. The solvable algebras of maximal rank occurring in maximal supergravities in diverse dimensions are described in some detail. A particular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
250
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(254 citation statements)
references
References 42 publications
2
250
0
2
Order By: Relevance
“…It turns out that these transformations are certain Cartan elements in K = G/H [27], that is they belong to O(1, 1) p ∈ K, with p = 1 for N = 5, p = 3 for N = 6, 8.…”
Section: Appendix: a Simple Determination Of The U-invariantsmentioning
confidence: 99%
“…It turns out that these transformations are certain Cartan elements in K = G/H [27], that is they belong to O(1, 1) p ∈ K, with p = 1 for N = 5, p = 3 for N = 6, 8.…”
Section: Appendix: a Simple Determination Of The U-invariantsmentioning
confidence: 99%
“…maximally non compact, forms of the corresponding U -duality groups, as it is the case for E 7(7) ). The maximal degree of the polynomial in the Iwasawa decomposition of E 7 (7) SU ( 8) in the 56 of E 7(7) is d = 27. On the other hand, the Iwasawa parametrization of axionic generators of E 7(7) , performed in [44], considers the maximal triangular subgroup of E 7 (7) , containing the D = 5 U -duality group G 5 ≡ G 5,Os = E 6(6) :…”
Section: N = 8 D = 4 Maximal (J Osmentioning
confidence: 99%
“…Such non compact forms of the Lie groups are relevant for supergravity [1,2,3,4,5,6,7,8]. Here the scalar sector of the theory is described by a non linear sigma model based on a non compact symmetric space with negative curvature G/K, where G is non compact and K is its maximal compact subgroup.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, Sen showed that all extremal black holes, both supersymmetric and non-supersymmetric (non-BPS), exhibit attractor behavior [2]: it is a result of the near-horizon geometry of extremal black holes, rather than supersymmetry. Since then, non-BPS attractors have been a very active field of research (see for instance [3,4,5,6,7,8,9,10,11,12,13,14,15]). In particular, a microstate counting for certain non-BPS black holes was proposed in [16].…”
Section: Introductionmentioning
confidence: 99%